2014
DOI: 10.3133/sir20145201
|View full text |Cite
|
Sign up to set email alerts
|

Water and nutrient budgets for Vancouver Lake, Vancouver, Washington, October 2010-October 2012

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In particular, PO 4 -P availability in Vancouver Lake may have had an indirect influence on summertime zooplankton community composition through the stimulation of cyanobacterial blooms. Increased orthophosphate concentrations during summer months in Vancouver Lake were most likely due to a combination of several processes, including wind driven sediment resuspension (Sheibley et al 2014), anoxia at the sediment-water interface (Lee et al 2015a), and possibly the release of PO 4 -P due to grazing (Frost et al 2004). Recently, Lee et al (2015a) demonstrated that peaks in PO 4 -P concentration were significantly associated with the occurrence and duration of large cyanobacterial blooms that occurred in Vancouver Lake during each summer from 2007 to 2009.…”
Section: Effects Of Eutrophication On Zooplankton Community Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, PO 4 -P availability in Vancouver Lake may have had an indirect influence on summertime zooplankton community composition through the stimulation of cyanobacterial blooms. Increased orthophosphate concentrations during summer months in Vancouver Lake were most likely due to a combination of several processes, including wind driven sediment resuspension (Sheibley et al 2014), anoxia at the sediment-water interface (Lee et al 2015a), and possibly the release of PO 4 -P due to grazing (Frost et al 2004). Recently, Lee et al (2015a) demonstrated that peaks in PO 4 -P concentration were significantly associated with the occurrence and duration of large cyanobacterial blooms that occurred in Vancouver Lake during each summer from 2007 to 2009.…”
Section: Effects Of Eutrophication On Zooplankton Community Dynamicsmentioning
confidence: 99%
“…Kend-all's tau (τ b ) was then used to examine concordance among sites and demonstrated no significant spatial differences in plankton community composition (n = 10 per site, p > 0.05) (Bollens & Rollwagen-Bollens 2009). Additionally, the depth at the end of the dock sampling site has been shown to be representative of the mean depth of the lake (Sheibley et al 2014). Based on these results, and ease of access, all subsequent sampling was conducted from the end of the dock located just south of Burnt Bridge Creek (Fig.…”
Section: Field Collectionsmentioning
confidence: 99%